Gc-Ms analysis and antibacterial activity of mangosteen leaf extracts against plant pathogenic bacteria - Alsultan, Qamar Mohammed Naji; Sijam, Kamaruzaman; Rashid, Tavga Sulaiman; Ahmad, Khairulmazmi (Scientific Research Publishing, 2016)
The potential of Garcinia mangostana as a biological control agent against plant pathogenic bacteria which decrease the quality and volume of crop production worldwide was assessed. Mangosteen leaves were extracted by maceration using chloroform, n-hexane, and methanol. For the in vitro antibacterial activity, two dissimilar species of plant pathogenic bacteria: Pseudomonas syringe pv. tomato and Xanthomonas oryzae pv. oryzae were acquired. Four different concentrations, 12.5, 25, 50, and 100 mg/ml were obtained through the cup-plate agar diffusion technique. Streptomycin sulphate at 30 μg/ml concentration was set as the positive control, whereas every respective solvent used in the leaf extraction was set as the negative control. The results have shown that, only methanol extract demonstrated antibacterial activity when tested on the plant pathogenic bacteria. The highest diameter of inhibition zones was observed in X. oryzae pv. oryzae, at all range of concentrations, followed by P. syringae pv. tomato. The least methanol extract concentration utilised in determination of minimum inhibitory concentration (MIC) assay was at 1.562 mg/ml, inhibiting X. oryzae pv. oryzae, followed by P. syringe pv. tomato at a concentration 3.125 mg/ml. Antibacterial impacts of the most effectual extract of mangosteen crude were supported by the existence of chemical components identified by GC-MS. Cycloartenol, Caryophyllene, Docosane, Phenol, 4,4-Methylenebis (2,6-di-tert-butylphenol) and Chromium were noted as key compounds in the mangosteen leaf extract, which were perhaps causing the antibacterial activity.